The environment. A human crisis. - Piburn, Michael
How old will you be after many years ? How will the world be different ? If you could choose, what things would you change between now and then ? What would you leave unchanged ? Social problems such a discrimination, pollution, crime, and poverty are the result of decisions made in the past. Are there solutions for these and other problems ?
Contents.
Keywords: Environnement